Penerapan Pendekatan Whole Language Dalam Pembelajaran Bahasa Indonesia Komponen Silent Reading Menggunakan Media Cerita Rakyat - Balista, Arahmana; Mudzanatun; Duwi Nuvitalia (Universitas Ngudi Waluyo, 2023)
Abstract The background that prompted this research was that almost all students in the high grades were able to read well so very few students experienced reading difficulties. However, there are still few students who are able to understand the text they read. In addition, learning has been carried out online in recent years which has resulted in students having low interest in reading. The objectives to be achieved in this study are to 1) Know the application of the whole language approach in teaching Indonesian the silent reading component in class V SDN 01 Protomulyo. 2) Knowing students' reading comprehension skills in understanding the contents of the text read. This type of research is descriptive qualitative with processing and data collection in accordance with the facts in the field. Data obtained from interviews, observations, tests and documentation. The data obtained were analyzed and presented in a descriptive form. The subjects of this study were fifth grade students at SDN 01 Protomulyo. The results of the study showed that fifth grade students were good at reading, it's just that their understanding of reading was still lacking. It was proven that at the first meeting before the whole language approach was implemented in class, the students' test results were still far from expectations. And the average at the time of the first meeting is also still low. In contrast to the second and third meetings, the average has experienced a good increase. At the first meeting, the average score in class V was 58. The second meeting, the average increased to 69. Finally, at the third meeting, the average increased to 80. Abstrak Latar belakang yang mendorong penelitian ini adalah hampir seluruh siswa yang ada di kelas tinggi sudah mampu membaca dengan baik sehingga sangat minim siswa yang mengalami kesulitan dalam membaca. Namun, masih sedikit siswa yang mampu memahami teks yang ia baca. Ditambah lagi pembelajaran dilakukan secara daring beberapa tahun terakhir yang mengakibatkan siswa memiliki minat baca yang rendah. Tujuan yang hendak dicapai dalam penelitian ini adalah untuk 1) Mengetahui penerapan pendekatan whole language dalam pembelajaran bahasa Indonesia komponen silent reading di kelas V SDN 01 Protomulyo. 2) Mengetahui kemampuan membaca pemahaman siswa dalam memahami isi teks yang dibaca. Jenis penelitian ini adalah deskriptif kualitatif dengan pengolahan dan pengambilan data sesuai dengan fakta di lapangan. Data diperoleh dari hasil wawancara, observasi, tes dan dokumentasi. Data yang diperoleh dianalisis dan disajikan dalam bentuk deskriptif. Subjek penelitian ini adalah siswa kelas V SDN 01 Protomulyo. Hasil penelitian menunjukkan bahwa siswa kelas V sudah baik dalam membaca, hanya saja pemahaman mereka dalam membaca masih dikatakan kurang. Terbukti pada pertemuan pertama sebelum diterapkan pendekatan whole language di kelas hasil tes siswa masih jauh dari harapan. Serta rata-rata pada saat pertemuan pertama juga masih rendah. Berbeda dengan pada saat pertemuan kedua dan ketiga rata-rata sudah mengalami peningkatan yang sudah baik. Pada pertemuan pertama rata-rata nilai di kelas V adalah 58. Pertemuan kedua rata-rata naik menjadi 69. Terakhir pada pertemuan ketiga rata-rata mengalami kenaikan menjadi 80.